Entrepreneurial developments and small scale industry contribution to Nigerian national development- A marketing interface - Ogechukwu, Ayozie Daniel (Information Management and Business Review, 2010)
In both developed and developing countries, the government is turning to small and medium scale industries and entrepreneurs, as a means of economic development and a veritable means of solving problems. It is a seedbed of innovations, inventions and employment. Entrepreneurship is as old as Nigeria and had contributed to the growth of the economy. Presently in Nigeria, SMEs assist in promoting the growth of the country’s economy, hence all the levels of government at different times have policies which promote the growth and sustenance of SMEs. This paper identifies the orientation of SME’s and entrepreneurial trends in Nigeria, tackles the operational definition and scopes, and describes the role of the Nigerian government as a participant, regulator and facilitator, both legally and politically in the growth of SMEs and entrepreneurship. It identifies the marketing problems of SMEs and entrepreneurships in Nigeria, the provision and enactment of beneficial and supportive laws, the provision of infrastructural facilities, constant man-power and development, direct financial assistance to SMEs and the establishment of finance institutions to support SMEs. It identifies the roles of SMEs in Nigeria’s development and growth. It discusses the entrepreneurial thoughts, problems and advance practical marketing solution. It concludes by clearly specifying the role of marketing to the survival of SMEs and entrepreneurship in Nigeria, and relevant recommendations. For SMEs to survive marketing practice and principles must be given prominence.